Global Civil Society Yearbook 2009: Poverty and Activism - Kumar, Ashwani; Scholte, Jan Aart; Kaldor, Mary; Glasius, Marlies; Seckinelgin, Hakan; Anheier, Helmut K (SAGE Publications, Limited, 2009)
Latest edition of this internationally renowned yearbook from its UCLA and LSE based editors.